Ergativity in President Buhari's (2015) Inaugural Speech: A Systemic Functional Approach (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
Understanding the language use in political discourse especially inaugural speeches is crucial because of the complex dynamics of power, ideology and communication in play in politics. This study investigates the ideological and pragmatic implications of ergative choices made in President Buhari’s 2015 inaugural speech. The speech was purposively selected because the 2015 inaugural speech is a speech that marked transition from the ruling party to the opposition. Due to the nature and size of the data, content analysis under qualitative research design was adopted. Findings reveal that in the speech, the choice of Medium over Agent and the use of “middle” clauses, made agency not be accounted for in some instances.  Also, the use of some descriptive words in the relational process such as terrifying force, mindless group, immediate concern, to describe Boko Haram while words such as eccentric and unorthodox used to describe the founder of Boko Haram suggests the communication of mixed messages. This paper concludes that linguistic choices made in political text are structured in such a way where the audience needs to pay attention to fully understand the actual message being communicated. This is usually the case because the language used in political text is designed to convey a surface meaning as well as a deep meaning.
Keywords: “effective” clauses; range; medium; agent; receptive voice